2016
DOI: 10.1242/dev.137000
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Wnt pathway genes wls, wnt9a, wnt5b, frzb and gpc4 in regulating convergent-extension during palate morphogenesis

Abstract: The Wnt signaling pathway is crucial for tissue morphogenesis, participating in cellular behavior changes, notably during the process of convergent-extension. Interactions between Wnt-secreting and receiving cells during convergent-extension remain elusive. We investigated the role and genetic interactions of Wnt ligands and their trafficking factors Wls, Gpc4 and Frzb in the context of palate morphogenesis in zebrafish. We describe that the chaperon Wls and its ligands Wnt9a and Wnt5b are expressed in the ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…Previous studies have showed that wls, wnt9a, wnt5b and gpc4 are expressed in ventral cartilage elements at the early time points of 55 h post-fertilization (hpf) and 72 hpf (Curtin et al, 2011; Rochard et al, 2016; Sisson et al, 2015). Sisson et al showed that gpc4 is expressed in the pharyngeal endoderm, neural crest and mesoderm while wnt5b is restricted to the neural crest and mesoderm (Sisson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have showed that wls, wnt9a, wnt5b and gpc4 are expressed in ventral cartilage elements at the early time points of 55 h post-fertilization (hpf) and 72 hpf (Curtin et al, 2011; Rochard et al, 2016; Sisson et al, 2015). Sisson et al showed that gpc4 is expressed in the pharyngeal endoderm, neural crest and mesoderm while wnt5b is restricted to the neural crest and mesoderm (Sisson et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mesenchymal expression of wls is necessary for the expansion and differentiation of chondrocytes to enable growth of Meckel’s cartilage (Rochard et al, 2016). The data underscores the spatiotemporal regulation of Wnt signaling in ventral cartilage development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations